Protected Organic Acid and Essential Oils for Broilers Raised Under Field Conditions: Intestinal Health Biomarkers and Cecal Microbiota - Bortoluzzi, Cristiano; Lahaye, Ludovic; Oxford, Jarred; Detzler, Derek; Eyng, Cinthia; Barbieri, Nicolle Lima; Santin, Elizabeth; Kogut, Michael Henry (Frontiers in Physiology, 2021)
The objective of the present study was to evaluate the effect of protected organic acids (OA) and essential oils (EO) [P(OA + EO)] on the intestinal health of broiler chickens raised under field conditions. The study was conducted on four commercial farms. Each farm consisted of four barns, two barns under a control diet and two tested barns supplemented with P(OA + EO), totaling 16 barns [8 control and 8 under P(OA + EO)]. The control group was supplemented with antibiotic growth promoters [AGP; Bacitracin Methylene Disalicylate (50 g/ton) during starter, grower and finisher 1, and flavomycin (2 g/ton) during finisher 2]. The tested group was supplemented with 636, 636, 454, and 454 g/ton of P(OA + EO) during starter, grower, finisher 1 and 2, respectively. Eighty birds were necropsied (40/treatment; 20/farm; and 5/barn) to collect blood, jejunal tissue, and cecal contents. The data were submitted to analysis of variance (ANOVA) (P < 0.05) or Kruskal-Wallis’ test and the frequency of antimicrobial resistant (AMR) genes was analyzed by Chi-Square test (P < 0.05). It was observed that the supplementation of P(OA + EO) reduced (P < 0.05) the histopathology scores, such as the infiltration of inflammatory cells in the epithelium and lamina propria and tended (P = 0.09) to reduce the serum concentration of calprotectin (CALP). The supplementation of P(OA + EO) reduced the serum concentration of IL-12 (P = 0.0001), IL-16 (P = 0.001), and Pentraxin-3 (P = 0.04). Additionally, P(OA + EO) maintained a cecal microbiota similar to birds receiving AGP. The substitution of AGP by P(OA + EO) reduced (P < 0.05) the frequency of four AMR genes, related to gentamicin (three genes), and aminoglycoside (one gene). Overall, the inclusion of P(OA + EO), and removal of AGP, in the diets of commercially raised broiler chickens beneficially changed the phenotype of the jejunum as shown by the lowered ISI scores which characterizes an improved intestinal health. Furthermore, P(OA + EO) significantly reduced the serum concentration of several inflammatory biomarkers, while maintaining the diversity and composition of the cecal microbiota similar to AGP fed chickens and reducing the prevalence of AMR genes.